Allergy and Immunotoxicology in Occupational Health - Otsuki, Takemi; Petrarca, Claudia; Di Gioacchino, Mario (Springer Singapore : Imprint: Springer, 2017)
This book offers a collection of the latest clinical and research findings related to allergies, one of the most frequently treated conditions in occupational medicine. The chapters not only cover asthma but also elaborate on contact dermatitis, rhinitis, and other allergic conditions, providing readers with a comprehensive overview of the substances disrupting autoimmunity and their effects on the human body. Allergy and Immunotoxicology in Occupational Health is a valuable resource for professionals and researchers in the occupational health sector, who will discover novel insights into immune effects, providing a foundation for future considerations of the health impairments caused by environmental and occupational exposure to these substances.
Keywords: Medicine.; Immunology.; Pharmacology.; Allergy.; Public health.; elektronické knihy; electronic books